KABOEL SOEADI: Seniman Lukis & Grafis Modernist - Henry H Loupias (Universitas Trisakti, 2003)
AbstractKaboel Soeadi is one of senior 'modernist' painter in Indoensia, visual elements and idioms like a line, shape, texture and color are just a main formal media to express his ideas. If there is an object in his painting, it is not more than a stimulant in his creative process and not as an effort to make more beautiful an objects or models